(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2024)
This report presents a proposal for a virtual stage lighting class, drawn up from the intersection of themes from light poetics studies and the words and expressions that describe natural light phenomena, based on the audio description script for the audiovisual: Caravana Time Lapse - Itatiaia National Park, prepared by audio describer Bell Machado, with consultancy from Emmanuelle Alkmin.I bring extracts from the script’s text to analyze how the colors and other aspects of the luminous atmospheres were created through the audio description from the film.The concept of chronotope in Mikhail Bakhtin (2020) brings theoretical inspiration to observe the temporal and spatial movements, of the film’s images in line with the semantic choices of the text. Such verbal creations of this audio description exemplify the chronotope of light on the mountain during a cycle, which goes from sunrise to deep night, intended for the enjoyment of blind people or people with low vision. I highlight the words that describe colors, nuances of shadows and refractions on a topography that interacts with the Park’s meteorological and atmospheric conditions. I explore the potential of a didactic synthesis, between audio description and natural light, emphasizing a reading of each chronotope of movements and moments in the text. I make inferences relating the nomenclatures of the two languages: the verbal one of audio description and the visual one of the stage lighting class.